2013
DOI: 10.1074/jbc.m112.416651
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate 6-O-Sulfotransferase Isoform-dependent Regulatory Effects of Heparin on the Activities of Various Proteases in Mast Cells and the Biosynthesis of 6-O-Sulfated Heparin

Abstract: Background: Heparin regulates mast cell proteases. Results: Both HS6ST-1 and HS6ST-2 are involved in 6-O-sulfation of heparin. The contents of tryptase and CPA in mast cells depend on 6-O-sulfation of heparin but chymase does not. Conclusion:The 6-O-sulfation pattern regulates differently the storage of MC-specific proteases. Significance: The fine structure of heparin may be essential for MC homeostasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 71 publications
2
11
0
Order By: Relevance
“…Hence, a likely explanation for the increase in mMCP6 levels in Ctr2 −/− cells could be that the increase in heparin may facilitate mMCP6 storage. In agreement with such a scenario, a previous study has shown that mMCP6 storage is severely defective in MCs lacking the expression of heparin 6-O-sulfotransferases (46). In further agreement, it is striking to note that the absence of Ctr2 led to increased expression of Hs6st1 accompanied by increased 6-O-sulfation of heparin.…”
Section: Discussionsupporting
confidence: 66%
“…Hence, a likely explanation for the increase in mMCP6 levels in Ctr2 −/− cells could be that the increase in heparin may facilitate mMCP6 storage. In agreement with such a scenario, a previous study has shown that mMCP6 storage is severely defective in MCs lacking the expression of heparin 6-O-sulfotransferases (46). In further agreement, it is striking to note that the absence of Ctr2 led to increased expression of Hs6st1 accompanied by increased 6-O-sulfation of heparin.…”
Section: Discussionsupporting
confidence: 66%
“…In addition, the heparin chain is cleaved by a ␤-endoglucuronidase called heparanase (3). The critical steps in heparin biosynthesis involve (i) the action of NDST2 (15,17,30), (ii) the action of GLCE (31), (iii) 6-O-sulfonation by HS6st1 and HS6st2 (32,33), and (iv) GAG chain modification by HS3st1 (34,35) (Fig. 1b).…”
Section: Heparan Sulfate (Hs)mentioning
confidence: 99%
“…5 ) seem to support the idea that CS/DS-E may play a certain role in the recovery process. Expression of HS6ST-2 was markedly increased on 2 days but expression of HS6ST-1 was not, suggesting that heparin-containing mast cells may be increased in the acute stage, because HS6ST-2 but not HS6ST-1 was shown to be involved mainly in the synthesis of highly sulfated heparin [42] .…”
Section: Discussionmentioning
confidence: 95%